Unusual Presentation of Influenza B Virus in a Neonate - Abdulrahman Al Zahrani; Ehab M. Hantash; Mohamed Abdoun; Syeda Naqvi (Dr. Sulaiman Al Habib Medical Journal)
The presentation of neonatal influenza B in neonates can vary from a mild self-limited disease to acute presentation carrying high morbidity and mortality. This report describes one case of influenza B in a neonate who presented with severe respiratory distress syndrome and acute renal failure.